Design and Development of Prototype Cylindrical Parabolic Solar Collector for Water Heating Application - Kulkarni, Hrushikesh Bhujangrao (Center of Biomass & Renewable Energy, Diponegoro University, 2016)
Concentrating collectors absorbs solar energy and convert it into heat for generating hot water, steam at required temperature, which can be further used for solar thermal applications. The developing countries like India where solar energy is abundantly available; there is need to develop technology for harnessing solar energy for power production, but the main problem associated with concentrating solar power technology is the high cost of installation and low output efficiency. To solve this problem, a prototype cylindrical parabolic solar collector having aperture area of 1.89 m2 is designed and developed using low cost highly reflecting and absorbing material to reduce initial cost of project and improve thermal efficiency. ASHRAE Standard 93, 1986 was used to evaluate the thermal performance and it was observed that this system can generate hot water at an average temperature of 500C per day with an average efficiency of 49% which is considerable higher than flat plate solar collectors. Hot water produced by this system can be useful for domestic, agricultural, industrial process heat applications.Article History: Received Sept 19, 2015; Received in revised form Dec 23, 2015; Accepted February 2, 2016; Available online How to Cite This Article: Bhujangrao, K.H. (2016). Design and Development of Prototype Cylindrical Parabolic Solar Collector for Water Heating Application. International Journal of Renewable Energy Development, 5(1), 49-55 http://dx.doi.org/10.14710/ijred.5.1.49-55Â